The Contextual of Waqf in Philosophy of Islamic Law Based on the Qur’an and Hadith - Qamariyanti, Yulia (Lambung Mangkurat Law Journal, 2016)
The Islamic law is the command of God revealed to the Prophet Muhammad. Islamic legal thought can be a discussion about the purpose of Islamic law (al- ahkaammaqaashid). Islam gives comprehensive guidance to human life covering all aspects of life towards the achievement of happiness, physical, spiritual, social, individual and the world hereafter. The philosophy of Islamic law is the rule, principle, Mabda’ rules which are used to control the Islamic community. These rules can be in the forms of the verses the Qur’an, Hadith, or can be the opinions of the Prophet’s friends and tabi’in, and may also be the opinion developed at a time in the life of the community of Muslims or Islam. In the history of Islam, endowments known since the time of the Prophet Muhammad as endowments were prescribed after the Prophet Muhammad was in Medina.